Can Gender and Age Impact on Response Pattern of Depressive Symptoms Among College Students? A Differential Item Functioning Analysis - de Sá Junior, Antonio Reis; Liebel, Graziela; Andrade, Arthur Guerra de; Andrade, Laura Helena; Gorenstein, Clarice; Wang, Yuan-Pang (Frontiers in Psychiatry, 2019)
Background: Self-reported depressive complaints among college students might indicate different degrees of severity of depressive states. Through the framework of item response theory, we aim to describe the pattern of responses to items of the Beck Depression Inventory-II (BDI-II), in terms of endorsement probability and discrimination along the continuum of depression. Potential differential item functioning of the scale items of the BDI-II is investigated, by gender and age, to compare across sub-groups of students. Methods: The 21-item BDI-II was cross-sectionally administered to a representative sample of 12,677 Brazilian college students. Reliability was evaluated based on Cronbach’s alpha coefficient. Severity (bi) and discrimination (a) parameters of each BDI-II items were calculated through the graded response model. The influence of gender and age were tested for differential item functioning (DIF) within the item response theory-based approach. Results: The BDI-II presented good reliability (α = 0.91). Women and younger students significantly presented higher likelihood of depression (cut-off > 13) than men and older counterparts. In general, participants endorsed more easily cognitive-somatic items than affective items of the scale. “Guilty feelings”, “suicidal thoughts”, and “loss of interest in sex” were the items that most likely indicated depression severity (b ≥ 3.60). However, all BDI-II items showed moderate-to-high discrimination (a ≥ 1.32) for depressive state. While two items were flagged for DIF, “crying” and “loss of interest in sex”, respectively for gender and age, the global weight of these items on the total score was negligible. Conclusions: Although respondents’ gender and age might present influence on response pattern of depressive symptoms, the measures of self-reported symptoms have not inflated severity scores. These findings provide further support to the validity of using BDI-II for assessing depression in academic contexts and highlight the value of considering gender- and age-related common symptoms of depression.